Penggunaan media flashcard pada pembelajaran kosakata bahasa inggris di sekolah dasar - Hamidah, Nisa; Saputra, Erwin Rahayu; Indihadi, Dian (Aksara: Jurnal Bahasa dan Sastra, 2023)
English as an international language has an important role in communication in the international sphere. This research is motivated by the lack of motivation to learn English in elementary school students and the difficulty of learning English vocabulary. The purpose of this study is to describe the use of flashcard media in learning English vocabulary. In this study, a qualitative descriptive method was used with a sample of 28 students at Public Elementary School 3 Banjarwangi, Garut, West Java. Data collection was carried out using observation techniques, interviews, and a literature review. From this research, data was generated that the use of flashcard media in learning professional vocabulary could increase students' motivation to learn and improve their understanding of professional vocabulary material. Nonetheless, learning motivation and increased understanding of English vocabulary needs to be in line with interesting and effective learning strategies.Keyword: flashcards, vocabulary, English language, Elementary school